2013
DOI: 10.1021/ie301414h
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Extraction of Synthetic Rutile from Modified Slag

Abstract: In this work, a new technique of modified-alkali leaching−dilute acid washing for extracting synthetic rutile from high-titanium slag is proposed. Most of the Ti components are enriched into the rutile phase during the modification, and rutile can be separated by alkali leaching−dilute acid washing. Thermodynamic analyses of the reactions occurring during the alkali leaching−dilute acid washing process were performed to provide a theoretical basis for rutile extraction from the modified slag. The calculated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The feasibility of the alkali leachingdilute acid washing process was evaluated by means of thermodynamic analysis. According to the relevant investigations [18][19][20][21][22][23][24], binary potential pH diagrams for Si-H2O, Al-H2O, Mg-H2O, V-H2O, Ca-H2O, Fe-H2O and Mn-H2O systems have been reported. It was found that Al2O3, MgO, V2O5, VO2, CaO, FeO and MnO could be leached by dilute acid, and SiO2 could be leached by alkali.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The feasibility of the alkali leachingdilute acid washing process was evaluated by means of thermodynamic analysis. According to the relevant investigations [18][19][20][21][22][23][24], binary potential pH diagrams for Si-H2O, Al-H2O, Mg-H2O, V-H2O, Ca-H2O, Fe-H2O and Mn-H2O systems have been reported. It was found that Al2O3, MgO, V2O5, VO2, CaO, FeO and MnO could be leached by dilute acid, and SiO2 could be leached by alkali.…”
Section: Methodsmentioning
confidence: 99%
“…According to the relevant literature [24] and Figure 3, it can be seen that SiO 2 and Al 2 O 3 in the slag can be theoretically leached by alkali. Thus, the TiO 2 content in the slag, SiO 2 extraction ratio and Al 2 O 3 extraction ratio were determined by chemical analysis.…”
Section: Alkali Leachingmentioning
confidence: 97%
See 1 more Smart Citation
“…[11][12][13] Most of these additives would be decomposed and release gasses during roasting. [14,15] Therefore, the roasting atmosphere includes not only oxygen but also the decomposition gas of additives. [16] However, the investigations on the decomposition characteristics of additives and the effect of the gasses decomposed from additives on vanadium recovery were seldom involved.…”
Section: Introductionmentioning
confidence: 99%
“…The separated rutile from slags can be further treated through hydrochloric acid leaching method for TiO 2 white pigment production or used as raw materials in titanium metallurgy. [10][11][12][13] The most important considerations of SCPS method are the selection and formation of Ti-enriched phases. The primary crystalline phase of the industrial Ti-BF slags is perovskite, the crystallization behaviors of which have been studied by many researchers.…”
Section: Introductionmentioning
confidence: 99%